Machine learning in clarifying the coupled effects of pore structure and nitrogen density on desalination capacity for capacitive deionization - Hao Kong; Hongshan Wang; Ming Gao; Qi Li; Ran Li; Yuchen Kang; Weilong Xiao; Tianqi Ao; Haiyan Mou; Wenqing Chen (Desalination, 2026)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

PFDA exposure promotes myocardial aging and fibrosis via hyperactivation of the MTORC1 signaling axis - Xiao Guang Chen; Ze Yu Liao; Yi Zhang; Ran Li (Food and Chemical Toxicology, 2026)

Potassium oxalate-activated bamboo charcoal: a green solution for constructing high-performance capacitive deionization electrodes for nitrate removal - Weilong Xiao; Rencheng Li; Ming Gao; Ran Li; Luwei Miao; Yufeng Da; Yang Bao; Ke Li; Tianqi Ao; Qiulin Yang; Xing Chen; Haiyan Mou; et al. (Desalination, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Soy milk fermented by Bacillus subtilis SP-8-5 and Lactiplantibacillus plantarum 4_3 exhibits sedative-hypnotic ability in vivo - Zhen Liu; Zhao-Ying Zeng; Yu-Jin Li; Bin Zhou; Shi-Yi Sun; Xia Ou; Hua Qi; Chen-Jian Liu; Xiao-Ran Li (Food Research International, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Ambient PM2.5 exposure is associated with clear cell renal cell carcinoma aggressiveness and promotes tumor progression through ROS-mediated AKT/HIF-2α signaling - Xiao-Hui Wu; Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Xue-Peng Jin; Fei Lin; Qing-Shui Zheng; Yong Wei; Shao-Hao Chen; Ning Xu; Xue-Yi Xue (Chemico-Biological Interactions, 2026)

Network pharmacology and cell experiments suggest natural algal astaxanthin as an anti-atherosclerotic agent via the PPARγ/NF-κB pathway - Yunmei Yin; Pei Wang; Zhen Zhang; Hongxiang Zhao; Meicong Xiao; Ran Chen; Kun Li; Shiqi Zhou; Rongqing Zhang (Algal Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

The tautomerism induced by the number of hydroxyl groups in COFs and its contribution to thorium adsorption - Shangjie Zhao; Long Chen; Xiaofan Ding; Ke Wang; Jicong Li; Ran Zhang; Jing Zhao; Ke Ma; Jinping Liu; Songtao Xiao (Journal of Environmental Sciences, 2026)

Screening and identification of soybean antioxidant peptides using Fe3O4-Modified carbon fibers - Xiao-Feng Chen; Xiang-Yu Huang; Hao-Ran Liu; Li Ding; Li Wen; Xu-Feng Wang; Zhou Xu; Yun-Hui Cheng; Mao-Long Chen (Food Bioscience, 2026)

A self-oxygenating, ROS-responsive nanoplatform potentiates sonodynamic-immunotherapy via STING activation in pancreatic cancer - Qiyi Feng; Xiao Wen; Chunxiu Xiao; Zhifan Wang; Qingqing Ran; Ling Wang; Sisi Yi; Xiuli Zheng; Zhaoyan Chen; Fangyuan Tian; Junjie Xiong; Haibo Wang; et al. (Chemical Engineering Journal, 2026)

Co-composting and organic amendments as tools to accelerate soil maturation in purple soils: Insights into soil properties and agricultural potential - Yuping Luo; Pengfei Du; Wenxiou Ran; Yiyuan Wei; Hui Wang; Shang Chen; Dan Song; Tao Liang; Ran Xiao (Journal of Environmental Management, 2026)

Carbon and phosphorus regeneration during organic matter decomposition in aquatic ecosystems: characteristics, mechanisms, and environmental effects - Chao Yin; Yan Zeng; Jingan Chen; Peng Liao; Jia Yu; Guangrong Ran; Baohua Xiao; Xudong Guo; Ziyan Zhang; Jingfu Wang; Haiquan Yang; Quan Yuan (Geochimica et Cosmochimica Acta, 2026)

Gelator-dependent crystalline network tolerance governs probiotic dispersion stability in oleogels through mechanisms involving rheology and crystallization kinetics - Shuai Chen; Zengliu Song; Ran Qiu; Suqiong Fang; Zhe Li; Ronghai Hu; Yong Cao; Jie Xiao (Food Research International, 2026)

Discovery of natural Nopol as promising antibacterial alternative with the capacity to suppress bacterial virulence and enhance plant immunity - Xiao-Di Chen; Yu-Mei Feng; Jun-Ning Ran; Wei Niu; Xin-Ming Yang; Xing-Yu Chen; Xiang Zhou; Song Yang (Pesticide Biochemistry and Physiology, 2026)

Construction of Li1-xMn2O4-Pb composite electrode ESIX system for efficient lithium recovery from high-sodium sulfate-type lithium-precipitation mother liquor - Jialu Chen; Jiang Gao; Ran Zhang; Zirui Wang; Qiang Ren; Fengfeng Gao; Zhonglin Zhang; Xiao Du; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2026)

Mechanical Deterioration and Crack Propagation Characteristics of Mudstone Under Cyclic Loading: Insights from Acoustic Emission Fractal Analysis - Qican Ran; Yunpei Liang; Chunfeng Ye; Xiao Song; Tengfei Ma; Zihan Chen (Rock Mechanics and Rock Engineering, 2026)

Interference of algal C-phycocyanin in type 2 diabetes: Mechanisms involving MAPK pathway activation and GLUT4 translocation - Hongxiang Zhao; Meicong Xiao; Yunmei Yin; Zhen Zhang; Yunyun Yang; Ran Chen; Kun Li; Pei Wang; Shiqi Zhou; Rongqing Zhang (Algal Research, 2026)

Toxoplasma GRA72 is Involved in Membrane-Associated Functions and Metabolic Homeostasis Revealed by Transcriptomic Analysis - Xin-Sheng Lu; Xing Tian; Jing Li; Chen-Ran Tian; Xing-Quan Zhu; Xiao-Nan Zheng (Acta Parasitologica, 2026)

Dietary bamboo vinegar powder supplementation mitigates the adverse effects of a high-starch diet on growth performance, liver health, and glucose-lipid metabolism in largemouth bass (Micropterus salmoides) - Weibin Lai; Zhangyi Xiao; Ran Yu; Linyi Li; Wenqian Chen; Yuan Gao; Manqi Yang; Liangliang Zhang; Liming Lu; Jianchun Jiang (Frontiers in Marine Science, 2026)
This study explored the potential of bamboo vinegar powder (BVP) to mitigate hepatic injury and metabolic disturbance induced by a high-starch diet in largemouth bass ( Micropterus salmoides ). Fish were distributed into three groups (with three replicates per group) and fed for 56 days with a basal diet (BD), a high-starch diet (CSD), and the BVP-supplemented diet (CSDB, added 2.0 g/kg BVP to the CSD diet), respectively. After the feeding trial, fish in the CSD group exhibited a significant decrease in weight gain rate (WGR) and an increased hepatosomatic index (HSI) ( P < 0.05). Concurrently, hepatic glucose and lipid metabolism of fish in the CSD group were suppressed, leading to the accumulation of hepatic lipids and glycogen, along with histopathological manifestations such as hepatic vacuolation and nuclear shift. Furthermore, immune competence and hepatic antioxidant status were also compromised. However, relative to the CSD group, fish in the CSDB group demonstrated significant improvements in growth performance, immune function, and liver injury. Furthermore, BVP upregulated the expression of nuclear factor erythroid 2-related factor 2 ( nrf2 , a key regulator of antioxidant defense) and downregulated the nuclear factor kappa B ( nf - κb , a central transcription factor in inflammation) ( P < 0.05). More importantly, BVP might improve the metabolism of hepatic glucose and lipid in fish, by suppressing gluconeogenesis and promoting glycolysis to optimize glucose metabolism, as well as by inhibiting lipogenesis and promoting both lipid transport and catabolism to enhance lipid metabolism. Notably, dietary BVP supplementation significantly altered hepatic metabolite profiles, affecting pathways such as alpha-linolenic acid and arachidonic acid metabolism, and increasing the levels of several lipid metabolites, including docosahexaenoic acid and phosphatidylethanolamine species, compared to the CSD group ( P < 0.05). Collectively, these results demonstrated that BVP improved growth performance, liver health, and glucose-lipid metabolism in largemouth bass fed a high-starch diet.

Leveraging industrial symbiosis benefits from multi-source heavy metal hazardous waste co-reutilization with industry kilns for anthropogenic metal recovery: Methods and applications - Long Wen; Luying Xiao; Yi Yao; Zhisong Ran; Yang Yue; Xiaojia Chen; Beijia Huang; Yao Wang (Journal of Cleaner Production, 2026)

Targeting stable desalination via harnessing in situ oxygen reduction reaction in capacitive deionization - Luwei Miao; Ran Li; Ming Gao; Ke Li; Weilong Xiao; Yang Bao; Haiyan Mou; Qiulin Yang; Wenqing Chen (Chemical Engineering Journal, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

One-step phase separation and magnetic retrieval of switchable natural deep eutectic solvents via Fe3O4@CA composites for rapid extraction of illegal non-steroidal anti-inflammatory drugs in herbal extracts - Jin-Yue Dong; Rong-Jie Wang; Qing Ran; Xiao-Bei Yang; Wen-Chao Han; Feng-Qi Dong; Di Chen (Sustainable Chemistry and Pharmacy, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

A multiscale risk operation and decision making model for inter-basin water diversion project under climate variability - Juan Chen; Zhen-ran Zhang; Yi-fan Liang; Xiao-hui Fan; Jian-qing Xie; Zhen Li; Ping-an Zhong (Environmental Research, 2026)

Thermo and LDL-responsive acrylated β-cyclodextrin based microspheres enable targeted oleanolic acid release and LDL removal for atherosclerosis therapy - Yujie Xiao; Xianda Liu; Ziyue Ling; Shifan Chen; Ran Wei; Weifeng Zhao; Changsheng Zhao (Chemical Engineering Journal, 2026)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Proteomic, metabolomic and lipidomic profiles provide insights on milk quality differences during heat treatment - Meiqing Chen; Ran Xiao; Shuang Du; Ashikur Rahman; Nan Zheng; Yangdong Zhang; Tianjiao Niu; Jiaqi Wang (Food Chemistry, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Profiling of Oryza Sativa Sulfotransferase Genes Associated with Oxyfluorfen and Fluroxypyr-Meptyl Metabolism - Li Qing Zeng; Xiao Yu Zhong; Nian Hua Teng; Xu Zhen Shi; Yi Zhuo Wang; Xi Ran Cheng; Ying Yu Zeng; Zhao Jie Chen (Tropical Plant Biology, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

Development of novel melatonin-isatin hybrids as multifunctional agents for Alzheimer’s disease - Ying-Ying Zhong; Jun‑Ze Deng; Qin Wang; Li Chen; Zi-Hang Yang; Ya-Mei Zhang; Lu‑Yi Zhou; Yi-Ran Li; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Dolomite reservoir differences in characteristics and controlling factors of grainstone shoal facies in Qixia Formation, Sichuan Basin - Benjian Zhang; Hualing Ma; Xiaojie Huang; Xihua Zhang; Xiao Chen; Fujie Jiang; Chen Xie; Yangui Chen; Ran Liu; Wei Wang; Haitao Sun (Carbonates and Evaporites, 2025)

A three-step process for purification and stability evaluation of analytical-grade phycocyanin from Spirulina - Hongxiang Zhao; Shilin Wu; Zhen Zhang; Ran Chen; Kun Li; Meicong Xiao; Yunmei Yin; Pei Wang; Rongqing Zhang (Algal Research, 2025)

Large-scale single tree information extraction of oil palm in Malaysia based on sub-meter visible light satellite images - Sen Zhang; Nan Li; Yaoping Cui; Jinwei Dong; Le Yu; Lishan Ran; Ziyue Chen; Jiqiang Niu; Wei Yan; Kasturi Devi Kanniah; Xiangming Xiao (Computers and Electronics in Agriculture, 2025)

Assessment of flood risk in jinsha river basin based on land use value and PSR model - Xiao Chen; Ran Zhai; Wen Fang; Liwen Xu; Lili Liang; Juanru Yang; Hanlin Man; Zhenyu Lv; Chao Wang; Deng Liu; Mengqing Cui (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Regulation of phytoplankton community by mesoscale eddies and the East Indian Coastal Current in the southwestern Bay of Bengal during the northeast monsoon - Hao Chen; Yuanli Zhu; Lihua Ran; Mengjia Zhang; Xiao Ma; Hongliang Li; Feng Zhou; W.N.C. Priyadarshani; Zhibing Jiang (Marine Environmental Research, 2025)

Response of nitrogen transformation and microbial community to aromatic compounds stress along heterotrophic nitrification and aerobic denitrification process - Weidong Xiao; Ran Sun; Lang Ran; Zherui Zhang; Xue Bai; Chen Lv; Maorui Zhang; Sihai Hu; Yaoguo Wu (Environmental Research, 2025)

“One stone, two birds”: A one-step sustainable dual-salt template route to synthesize glucose-derived porous carbon towards ammonium ion removal via capacitive deionization - Luwei Miao; Ming Gao; Ran Li; Ke Li; Weilong Xiao; Rencheng Li; Tianqi Ao; Yunjia Ling; Haiyan Mou; Wenqing Chen (Desalination, 2025)

Harnessing the power of lignin from Litsea cubeba fruit residues: Characterization and valorization - Kaili Zhang; Xiao Jiang; Ran Tao; Jingcong Xie; Jian Zhao; Ning Zhang; Yicun Chen; Yangdong Wang; Kui Wang; Jianchun Jiang (Biomass and Bioenergy, 2025)

The early Holocene vegetation history and quantitative reconstruction of climate in the Chahanur Lake, Inner Mongolia Plateau, China - Xu-Ran Zhang; Hua-Yong Zhang; Zhong-Yu Wang; Hao Chen; Xiao-Chang Wu; Zhao Liu (Palaeoworld, 2025)

LLTO-based electrodes for selective lithium extraction from high Mg2+/Li+ brines: Performance and mechanistic insights - Ran Zhang; Jialu Chen; Qian Xu; Beichen Sun; Xiao Du; Shanxia Luo; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2025)

Electrostatic-modulated assembly of charged COF nanosheets into high-performance nanofiltration-based desalination membranes - Shan Luo; Ran Chen; Ruiyuan Zeng; Dai Shi; Youqing Tian; Jiamei Sun; Zifan Song; Yuanhui Xiao; Jiashu Yuan; Jianghuan Shi; Haixiong Liu; Hanyang Liu; et al. (Chemical Engineering Journal, 2025)

Optimizing air quality forecasting with OSSE: Assessing the assimilation of aerosol species data via multi-resolution observation network design in the WRF-Chem and 3DVAR frameworks - Xiao Chen; Wei You; Ran Duan; Mingzhen Gu; Zengliang Zang; Jiali Luo (Atmospheric Research, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Optimizing fertilization enhances sustainable vegetable production: combining on-farm composting and biochar application to improve vegetable yield, soil health, and socio-economic benefits - Bihui Tang; Pingping Ye; Xu Luo; Xinyi Yang; Tao Liang; Anle Chen; Duan Yu; Xiaozhong Wang; Ran Xiao (Journal of Cleaner Production, 2025)

Effect of anticyclonic eddies on the production and emission of marine dimethylsulfide in the northern South China Sea - Jin-Wei Wu; Feng Xu; Shi-Bo Yan; Gao-Bin Xu; Yu-Cheng Jiang; Xiao-Ran Li; Xing Zhai; Li-Min Zhou; Hong-Hai Zhang; Zhao-Hui Chen (Global and Planetary Change, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The Association of Blood Cobalt Levels with Cardiovascular and Chronic Kidney Diseases: Mediating Role of Inflammatory Indicators (SII, NLR, PLR, NMLR, and LMR) - Bei-Bei Lu; Qian Luo; Xiao-Lin Yuan; Qing-Song Chen; Jing-Yang Ran; Xing-Wei Zhe; Xiao-Hui Liao (Cardiovascular Toxicology, 2025)

Machine learning-based prediction of desalination capacity of electrochemical performance of nitrogen-doped for capacitive deionization - Hao Kong; Ming Gao; Ran Li; Luwei Miao; Yuchen Kang; Weilong Xiao; Wenqing Chen; Tianqi Ao; Haiyan Mou (Desalination, 2025)

Trichothecroamides A‒F, antifungal amides from potato associated fungus Trichothecium crotocinigenum - Qiong Chen; Ao-Ran Xu; Bao-Bao Shi; Xiao-Fang Zhang; Ji-Kai Liu; Tao Feng (Phytochemistry, 2025)

Constructing and Evaluating Predictors for Data-Driven PM2.5 Forecasting Models - Ran-Ran He; Yu-Qiao Chen; Lei Tian; Lei Shan; Xiao-Shuang Sang (International Journal of Environmental Research, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Indian ocean-type mantle domain in the Carboniferous Qushiman ophiolite in the Northern Pamir: Significance for the intra-oceanic subduction in the Paleo-Tethys Ocean - Yan Jing; Chuan-Lin Zhang; Chen Wang; Masumeh Sargazi; Zhi-Hao Song; Yi-kang Quan; Zhi-Kai Xu; Xiao-Qiang Liu; Hong-Ran Wang (Chemical Geology, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Paleoceanographic and paleoenvironmental changes in the high-latitude Southern Ocean during late Quaternary: progress and prospects based on the Chinese Antarctic Expeditions - Li Wu; Rujian Wang; Wenshen Xiao; Qingmiao Li; Kaitao Ni; Ran Xu; Yi Chen (Acta Oceanologica Sinica, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Chronic intermittent hypoxia modulates energy metabolic pathways and improves hypoxia tolerance capacity in golden pompano, Trachinotus blochii - Geng Hui Fang; Xiao Li Zhou; Chun Li Ran; Chun Xiu Jin; Shao Yang Bu; Yue Chen; Yong Gong; Zeng Tan Hu; Fei Biao Song; Jian Luo; Jun Long Sun (Science of The Total Environment, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Cxcl9 modulates aging associated microvascular metabolic and angiogenic dysfunctions in subcutaneous adipose tissue - Xin Fu; Yu Zhao; Xiwei Cui; Siyuan Huang; Yanze Lv; Chen Li; Fuxing Gong; Zhigang Yang; Xiaonan Yang; Ran Xiao (Angiogenesis, 2025)

Immobilization and stabilization of D-allulose 3-epimerase for continuous D-allulose synthesis in packed-bed reactors - Ziqun Xiao; Bo Jiang; Jingjing Chen; Longbei Xiang; Ran Zhang (Food Bioscience, 2025)

Impact of residual antibiotics on microbial decomposition of livestock manures in Eutric Regosol: Implications for sustainable nutrient recycling and soil carbon sequestration - Linfa Fang; Prakash Lakshmanan; Xiaoxuan Su; Yujia Shi; Zheng Chen; Yu Zhang; Wei Sun; Junxi Wu; Ran Xiao; Xinping Chen (Journal of Environmental Sciences, 2025)

Corrigendum to “Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing” [Carbohydr. Polym. 343 (2024) 122492 - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2025)

Targeting modulation of intestinal flora through oral route by an antimicrobial nucleic acid-loaded exosome-like nanovesicles to improve Parkinson’s disease - Weitong Cui; Zhiyong Guo; Xingyu Chen; Ran Yan; Wenjuan Ma; Xiao Yang; Yunfeng Lin (Science Bulletin, 2024)

Functionalized mesoporous biosilica for immobilizing D-allulose 3-epimerase: A multienzyme cascade strategy for calorie reduction in fruit tea drinks - Ziqun Xiao; Ran Zhang; Longbei Xiang; Bo Jiang; Jingjing Chen (Food Bioscience, 2024)

Effects of oyster shell addition on shrimp aquaculture and the dynamic succession of surface biofilm microbial communities - Xianke Huang; Guoqiang Xiao; Xiang Zhang; Shuangshuang Teng; Min Li; Yilong Cai; Ran Chen; Xiaolin Huang (Frontiers in Marine Science, 2024)
Introduction In the context of Litopenaeus vannamei aquaculture, the incorporation of oyster shells has proven beneficial for enhancing water quality and the growth conditions of the shrimp. Nonetheless, the specific effects of in-situ water treatment using oyster shells on water quality and shrimp growth, along with the composition and succession dynamics of the microbial community within oyster shell biofilms, have yet to be thoroughly investigated. Methods This study established control, low-concentration, and high-concentration oyster shell addition groups to emulate the in-situ water treatment environment with oyster shells, with the objective of elucidating the impacts of oyster shell addition on the aquaculture setting. Results The results showed that the addition of oyster shells could significantly improve the length ( F = 12.248, P = 0.005 ), weight( F = 138.234, P < 0.001 ), and survival rate ( F = 15.248, P < 0.001 ) of shrimp, while there were no significant differences in the length ( F = -1.233, P = 0.267 ) and survival rate ( F = -2.143, P = 0.076 ) between the high and low concentration groups. Additionally, oyster shell addition resulted in elevated phosphate levels ( F = 74.92, P < 0.001 in Day 70), diminished nitrite levels ( F = 5.276, P = 0.031 in Day 56), and increased nitrate concentrations ( F = 9.421, P = 0.006 in Day 70). Within the biofilms, the relative abundances of Ruegeria, Tenacibaculum , BD2- 11_terrestrial_group , and Kapabacteriales exhibited significant declines over time, whereas the relative abundance of Nitrospira demonstrated a marked increase, ultimately emerging as the predominant bacterium (Relative abundance 31.8%) in the biofilms during the latter stages of the experiment. Nitrospira also exhibited a notably higher relative abundance in the microbial community of the experimental water group relative to the control group ( F = 2.265, P = 0.001 ). Discussion The biofilm provided conditions for the proliferation of Nitrospira , thereby accelerating the transformation of nitrite into nitrate in the aquaculture system, which subsequently improved the shrimp farming conditions. This research offers valuable insights for the application of oyster shells in shrimp farming and contributes to the theoretical underpinnings necessary for advancing our understanding of the mechanisms through which oyster shell biofilms enhance water quality and foster shrimp health.

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Different responses of individuals, functional groups and plant communities in CSR strategies to nitrogen deposition in high-altitude grasslands - Xueqi Li; Ying Li; Hao Shen; Shuai Li; Zhenzhen Zhao; Jiannan Xiao; Ran Zhang; Hang Shi; Hui Zuo; Tu Danjia; Guoming Chen; Xueli Zhou; et al. (Science of The Total Environment, 2024)

Selective increase of antibiotic-resistant denitrifiers drives N2O production in ciprofloxacin-contaminated soils - Linfa Fang; Yue Deng; Prakash Lakshmanan; Weibing Liu; Xiufeng Tang; Wenxin Zou; Tong Zhang; Xiaozhong Wang; Ran Xiao; Jinbo Zhang; Xinping Chen; Xiaoxuan Su (Journal of Hazardous Materials, 2024)

A conductive ionogel with Stretchability, low hysteresis and adjustable adhesion for Air/Underwater mechanosensing - Chuanjiang Zhou; Xiao Song; Ran Wei; Shengjie Liu; Zhaoqiang Wu; Hong Chen (Chemical Engineering Journal, 2024)

Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2024)

Contribution to energy conservation and quality improvement of frozen pork via contact/contactless immersion freezing in NaCl solution - Yu Zhou; Xia Yu; Ran Xiao; Li-fang Zou; Qing-fei Du; Fei Ma; Cong-gui Chen (Meat Science, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Deciphering the key factors affecting pesticide residue risk in vegetable ecosystem - Daiwei Liu; Tongtong Chen; Yahui Gong; Xuanjing Chen; Wei Zhang; Ran Xiao; Yuheng Yang; Tong Zhang (Environmental Research, 2024)

Progress toward adsorption mechanism exploration method for capacitive deionization: Experimental, mathematical model, computational chemistry and machine learning - Luwei Miao; Ming Gao; Weilong Xiao; Yuchen Kang; Ran Li; Hao Kong; Haiyan Mou; Wenqing Chen; Tianqi Ao (Desalination, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

B/N modified carbon nanofiber mesh covered with layered double hydroxide for large current overall water splitting - Ji Qi; Chunqi Zhu; Jianing Hu; Shuai Ran; Tauqeer Ahmad; Siraj Ullah; Lixu Chen; Yi Chen; Yuqing Xia; Xue Sun; Chuang Li; Xiao Chen; et al. (Fuel, 2024)

Fibroblast growth factor receptor 4 deficiency in macrophages aggravates experimental colitis by promoting M1-polarization - Luyao Shen; Cong Wang; Ran Ren; Xudong Liu; Dongqin Zhou; Yu Chen; Yu Zhou; Juan Lei; Yang Xiao; Nan Zhang; Huakan Zhao; Yongsheng Li (Inflammation Research, 2024)

Multi-GNSS broadcast ephemeris errors assessment and weight determination of different constellations for SPP - Hang Shen; Ran Li; Shuhui Li; Jingbin Liu; Xiao Chen; Jiajia Xu (Advances in Space Research, 2024)

Casein/butyrylated dextrin nanoparticles and chitosan stabilized bilayer emulsions as fat substitutes in sponge cakes - Han Tao; Xiao-Han Fang; Pin Chen; Bao-Qiu Yang; Ran Feng; Bao Zhang (Food Chemistry, 2024)

Mn-O bond Engineering Mitigating Jahn-Teller Effects of Manganese Oxide for Aqueous Zinc-ion Battery Applications - Meng Xie; Xiao Zhang; Ran Wang; Yang Jiao; Zhiwei Shu; Sunpeng Shan; Yuhong Bian; Hongjun Lin; Jianrong Chen; Yanchao Xu (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

New insights into microbial community for simultaneous removal of carbon and nitrogen via heterotrophic nitrification aerobic denitrification process - Weidong Xiao; Guangcai Meng; Chengzhen Meng; Ran Sun; Sihai Hu; Mengying Yi; Xue Bai; Chen Lv; Yaoguo Wu (Journal of Environmental Chemical Engineering, 2024)

Systemic evaluation of novel acaricide hexythiazox for bioactivity improvement and risk reduction at the enantiomer level - Ping Zhang; Furong Yang; Lulu Ran; Cancan Yang; Can Tang; Xiaojiang Ke; Juanni Chen; Wei Xiao; Lin He; Zhifeng Xu (Science of The Total Environment, 2024)

Methyl benzoate-related compounds as potential repellents and fumigants for the control of cigarette beetle, Lasioderma serricorne (F.) - Junli Xiao; Jianbo Jin; Shanyi Chen; Jianfeng Zhang; Peijian Cao; Li-Juan Mao; Ran Li (Journal of Stored Products Research, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Storage, form, and influencing factors of karst inorganic carbon in a carbonate area in China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; et al. (Science China Earth Sciences, 2024)

Leucine improves dietary protein use efficiency by regulating protein synthesis by activating amino acid transporters and the mTORC1 pathways in Chinese mitten crab (Eriocheir sinensis) - Ming-Qi Song; Qiu-Ran Yu; Er-Chao Li; Ying Song; Xin-Yu Cai; Yu-Xiang Huang; Chuan-Jie Qin; Xiao-Dan Wang; Jian-Guang Qin; Li-Qiao Chen (Aquaculture, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Production of carbon nanotubes via catalytic pyrolysis of polyethylene over Ni/ZSM-5 prepared by ethylene glycol assisted impregnation - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Tao-li Huhe; Hao-Ran Yuan; Yong Chen (Fuel, 2024)

A new cyclohexenone derivative from phomopsis sp. XM-01 - Cheng-Yao Wang; Dong Gan; Chen-Zhe Li; Li Zhu; Xiao-Ran Zhang; Ya-Ni Li; Xiu-Hong Wu; Hao Zhou; Le Cai (Natural Product Research, 2024)

Grain-size, coarse fraction lithology and clay mineral compositions of surface sediments from Ross Sea, Antarctica: implications for their provenance and delivery mode - Li Wu; Longwei Li; Rujian Wang; Hebin Shao; Yi Chen; Zipei Lin; Yue Liu; Wenshen Xiao; Ran Xu (Frontiers in Marine Science, 2024)
Knowledge on spatial distribution, provenance and delivery mode of surface sediment aids in interpretation of nearby sediment records for paleoenvironmental reconstruction. Such knowledge, however, remains largely unknown for the modern Ross Sea, Antarctica: a key region for understanding the dynamical behavior of Antarctic Ice Sheet over geological past. In this study, we address this gap by analyzing the grain-size distribution, coarse fraction (>250 μm) lithology, and clay mineralogy of a set of surface sediment samples covering the whole Ross Sea continental shelf. Our data reveals that the sediments were mostly delivered by icebergs and bottom currents. Iceberg delivery was significantly controlled by factors such as water depth, proximity to the iceberg sources, and invasion of the Modified Circumpolar Deep Water. Bottom current activity was stronger in the Western Ross Sea (WRS) than in the Eastern Ross Sea (ERS), controlled by the formation and transport of Dense Shelf Water. Three major sorts of coarse fraction were identified, including the quartz-rich Iceberg Rafted Detritus (IRD) originating from West Antarctic glaciers and primarily distributed in the ERS, the mafic rocks-rich IRD from the Ferrar Group as well as the McMurdo Volcanic Group and mainly found in the WRS, and deformed silt traced back to the grounding zone of the David Glacier-Dragalski Ice Tongue system. The distribution of clay minerals is dominated by a distinct binary mixing pattern. Smectite and kaolinite are mainly present in the ERS, derived from beneath the West Antarctic Ice Sheet. Higher illite and chlorite contents were found offshore of the Southern Victoria Land, derived from the East Antarctic craton. Overall, these results demonstrate that the glaciers draining into Ross Sea from both the East and West Antarctic Ice Sheets are highly dynamical in the context of modern climate conditions, with implications for potential contribution to future sea level rise.

Dryness stress weakens the sustainability of global vegetation cooling - Zilin Li; Xiaoyong Bai; Qiu Tan; Cuiwei Zhao; Yangbing Li; Guangjie Luo; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; Fengjiao Song; et al. (Science of The Total Environment, 2024)

Identifying cadmium and lead co-accumulation from living rice blade spectrum - Shuangyin Zhang; Teng Fei; Yiyun Chen; Jiaxin Yang; Ran Qu; Jian Xu; Xiao Xiao; Xuejun Cheng; Zhongzheng Hu; Xuedong Zheng; Dengzhong Zhao (Environmental Pollution, 2023)

In-situ introduction of CePO4 for stabilizing electrocatalytic activity of quasi-MOF with partially missing C≡N skeleton - Shuke Li; Meng Xie; Xiao Zhang; Nana Wang; Ran Wang; Yanchao Xu; Hongjun Lin; Yang Jiao; Jianrong Chen (Chemical Engineering Journal, 2023)

Spring photosynthetic phenology of Chinese vegetation in response to climate change and its impact on net primary productivity - Yingying Xue; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Min Liu; et al. (Agricultural and Forest Meteorology, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

Design of a novel chimeric peptide via dual blockade of CD47/SIRPα and PD-1/PD-L1 for cancer immunotherapy - Zheng Hu; Wanqiong Li; Shaomeng Chen; Danhong Chen; Ran Xu; Danlu Zheng; Xin Yang; Shuzhen Li; Xiuman Zhou; Xiaoshuang Niu; Youmei Xiao; Zhuoying He; et al. (Science China Life Sciences, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Carbon nanotubes production from catalytic pyrolysis of polyethylene over nickel-based catalysts: The influence of support materials - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Hao-Ran Yuan; Yong Chen (Fuel, 2023)

Nitrate_dependent suberization regulates cadmium uptake and accumulation in maize - Anle Chen; Tong Liu; Yan Deng; Ran Xiao; Tong Zhang; Yuan Wang; Yuheng Yang; Prakash Lakshmanan; Xiaojun Shi; Fusuo Zhang; Xinping Chen (Science of The Total Environment, 2023)

Impacts of EDTA on the fate of nutrients and heavy metals during the hydrothermal carbonization of poultry manure - Xuhao Chen; Xiaoxia Fan; Kunpeng Gao; Yang Cheng; Ke Zhang; Liyuan Liu; Lingfa Fang; Jong-Hwan Park; Xinping Chen; Ran Xiao (Journal of Environmental Chemical Engineering, 2023)

Ag@Bi5O7I nanoparticles deposited on Bi(OH)3 nanosheets for boosting photocatalytic antibacterial activity under visible light irradiation - Qinghan Chen; Li Wang; Dehui He; Bo Xiao; Xia Ran; Rong Li; Hong Xu; Jian Feng (Journal of Environmental Chemical Engineering, 2023)

Occurrence profiling and environmental risk assessment of veterinary antibiotics in vegetable soils at Chongqing region, China - Linfa Fang; Chengyu Chen; Fen Zhang; Esmat F. Ali; Binoy Sarkar; Jörg Rinklebe; Sabry M. Shaheen; Xinping Chen; Ran Xiao (Environmental Research, 2023)

Yellow Petal locus GaYP promotes flavonol biosynthesis and yellow coloration in petals of Asiatic cotton (Gossypium arboreum) - Yaohua Li; Lingfang Ran; Tong Mo; Nian Liu; Jianyan Zeng; Aimin Liang; Chuannan Wang; Qingwei Suo; Zhong Chen; Yi Wang; Nianjuan Fang; Shijia Xu; et al. (Theoretical and Applied Genetics, 2023)

A new cyclopentenone derivative from Trichoderma atroviride HH-01 - Li Zhu; Jia-Peng Wang; Feng Hao; Dong Gan; Xiao-Ran Zhang; Chen-Zhe Li; Cheng-Yao Wang; Liang Zhang; Le Cai (Natural Product Research, 2023)

Optical Coherence Tomography in Cerebrovascular Disease: Open up New Horizons - Ran Xu; Qing Zhao; Tao Wang; Yutong Yang; Jichang Luo; Xiao Zhang; Yao Feng; Yan Ma; Adam A. Dmytriw; Ge Yang; Shengpan Chen; Bin Yang; et al. (Translational Stroke Research, 2023)

Interleukin-17D mediates Vibrio harveyi infection-related changes in Tegillarca granosa though activation of activator protein 1 in vivo - Qiujin Wang; Guoqiang Xiao; Gaoyu Hu; Ran Chen; Min Li; Shuangshuang Teng (Aquaculture, 2023)

Insights into carbon loss reduction during aerobic composting of organic solid waste: A meta-analysis and comprehensive literature review - Pingping Ye; Linfa Fang; Dan Song; Muyuan Zhang; Ronghua Li; Mukesh Kumar Awasthi; Zengqiang Zhang; Ran Xiao; Xinping Chen (Science of The Total Environment, 2023)

Three-dimensional structure of mesoscale eddies and their interaction with Kuroshio based on observations from a CPIES array - Qiang Ren; Yansong Liu; Ran Wang; Feng Nan; Jianfeng Wang; Xinyuan Diao; Zifei Chen; Fei Yu; Chuangzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiao-Hua Zhu (Frontiers in Marine Science, 2023)
Mesoscale eddies are widespread in the oceans; however, tracking and observing them remains a challenge. Additionally, there are few studies of eddy–Kuroshio interactions based on large-scale in situ data. Data from a large array of 39 CPIESs deployed around the Luzon Strait in 2018–2019 (12 deployed east of Taiwan within a 3 × grid) were used to reveal the three-dimensional structure of mesoscale eddies and their interaction with Kuroshio. The results show a strengthening (weakening) of the tilt of the pycnocline, which has also caused a deeper (shallower) pycnocline in eastern Taiwan following an anticyclonic (cyclonic) interaction with Kuroshio, which resulted in a strengthening (weakening) of the Kuroshio. During the anticyclonic eddy impinging Kuroshio, the downward (upward) movement at the center of the anticyclonic eddy (Kuroshio) results in a positive (negative) anomaly structure for temperature, with corresponding positive (negative) anomalies for salinity above 600 m in the intermediate layer and negative (positive) anomalies below 600 m. In contrast, when the cyclonic eddies interact with the Kuroshio, the temperature and salinity anomalies change simultaneously, with the temperature showing an overall negative anomaly and the salinity showing a negative and positive anomaly above and below 600 m, respectively. The research in this study provides the basis for further research on energy exchange during eddy–Kuroshio interactions.

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

Impacts of hydraulic conditions on microplastics biofilm development, shear stresses distribution, and microbial community structures in drinking water distribution pipes - Xiao Chen; Xiao-ying Lian; Yi Wang; Sheng Chen; Yi-ran Sun; Guo-lin Tao; Qiao-wen Tan; Jing-chun Feng (Journal of Environmental Management, 2023)

Immune responses of hemocytes in the blood clam Tegillarca granosa in response to in vivo Vibrio harveyi infection - Qianyuan Yang; Guoqiang Xiao; Ran Chen; Xiaolin Huang; Shuangshuang Teng (Fish & Shellfish Immunology, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Three new unsaturated fatty acids from marine-derived fungus Aspergillus sp. SCAU150 - Ting Zhao; Xiao-Yong Zhang; Ran-Sha Deng; Zhen Tan; Guang-Ying Chen; Xu-Hua Nong (Natural Product Research, 2022)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Human activity and climate change triggered the expansion of rocky desertification in the karst areas of Southwestern China - Chaojun Chen; Daoxian Yuan; Hai Cheng; Tsailuen Yu; Chuanchou Shen; R. Lawrence Edwards; Yao Wu; Siya Xiao; Jian Zhang; Tao Wang; Ran Huang; Ziqi Liu; et al. (Science China Earth Sciences, 2021)

Biotransformation of Phlorizin by Eurotium cristatum to Increase the Antioxidant and Antibacterial Activity of Docynia indica Leaves - Jie Xie; Jiang Chen; Xue-ran Mei; Ming-jun Zhu; Xue-li Li; Juan Du; Xiao-yu Zhang (Current Microbiology, 2021)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

Medial Preoptic Area Modulates Courtship Ultrasonic Vocalization in Adult Male Mice - Shu-Chen Gao; Yi-Chao Wei; Shao-Ran Wang; Xiao-Hong Xu (Neuroscience Bulletin, 2019)

Bituminous coal combustion and Xuan Wei Lung cancer: a review of the epidemiology, intervention, carcinogens, and carcinogenesis - Jinhui Li; Jinjun Ran; Lung-chi Chen; Max Costa; Yunchao Huang; Xiao Chen; Linwei Tian (Archives of Toxicology, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Genome-Wide QTL Analysis Identified Significant Associations Between Hypoxia Tolerance and Mutations in the GPR132 and ABCG4 Genes in Nile Tilapia - Hong Lian Li; Xiao Hui Gu; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

Characterization and evaluation of a peptide-based siRNA delivery system in vitro - Baoling Chen; Kimoon Yoo; Wen Xu; Ran Pan; Xiao Xia Han; P. Chen (Drug Delivery and Translational Research, 2017)

Ultrastructure of ellipsoidal magnetotactic multicellular prokaryotes depicts their complex assemblage and cellular polarity in the context of magnetotaxis - Pedro Leão; Yi‐Ran Chen; Fernanda Abreu; Mingling Wang; Wei‐Jia Zhang; Ke Zhou; Tian Xiao; Long‐Fei Wu; Ulysses Lins (Environmental Microbiology, 2017)
Summary Magnetotactic multicellular prokaryotes (MMPs) consist of unique microorganisms formed by genetically identical Gram‐negative bacterial that live as a single individual capable of producing magnetic nano‐particles called magnetosomes. Two distinct morphotypes of MMPs are known: spherical MMPs (sMMPs) and ellipsoidal MMPs (eMMPs). sMMPs have been extensively characterized, but less information exists for eMMPs. Here, we report the ultrastructure and organization as well as gene clusters responsible for magnetosome and flagella biosynthesis in the magnetite magnetosome producer eMMP Candidatus Magnetananas rongchenensis. Transmission electron microscopy and focused ion beam scanning electron microscopy (FIB‐SEM) 3D reconstruction reveal that cells with a conspicuous core‐periphery polarity were organized around a central space. Magnetosomes were organized in multiple chains aligned along the periphery of each cell. In the partially sequenced genome, magnetite‐related mamAB gene and mad gene clusters were identified. Two cell morphologies were detected: irregular elliptical conical ‘frustum‐like’ (IECF) cells and H‐shaped cells. IECF cells merge to form H‐shaped cells indicating a more complex structure and possibly a distinct evolutionary position of eMMPs when compared with sMMPs considering multicellularity.

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Magnolol pretreatment attenuates heat stress-induced IEC-6 cell injury - Chen Mei; Sha-sha He; Peng Yin; Lei Xu; Ya-ran Shi; Xiao-hong Yu; An Lyu; Feng-hua Liu; Lin-shu Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

Fragment virtual screening based on Bayesian categorization for discovering novel VEGFR-2 scaffolds - Yanmin Zhang; Yu Jiao; Xiao Xiong; Haichun Liu; Ting Ran; Jinxing Xu; Shuai Lu; Anyang Xu; Jing Pan; Xin Qiao; Zhihao Shi; Tao Lu; et al. (Molecular Diversity, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

True-amplitude wavefield separation using staggered-grid interpolation in the wavenumber domain - Qi-Zhen Du; Ming-Qiang Zhang; Xiao-Ran Chen; Xu-Fei Gong; Cheng-Feng Guo (Applied Geophysics, 2014)

An efficient multistep ligand-based virtual screening approach for GPR40 agonists - Sihui Yao; Tao Lu; Zifan Zhou; Haichun Liu; Haoliang Yuan; Ting Ran; Shuai Lu; Yanmin Zhang; Zhipeng Ke; Jinxing Xu; Xiao Xiong; Yadong Chen (Molecular Diversity, 2014)

A new oleanane-type triterpenoidal saponin from Pulsatilla chinensis - Zhan Shu; Zhong Chen; Yan-li Liu; Wei-feng Zhu; Yu-lin Feng; Qiong-ming Xu; Xiao-ran Li; Shi-lin Yang (Natural Product Research, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Natural populations of lactic acid bacteria in douchi from Yunnan Province, China - Chen-jian Liu; Fu-ming Gong; Xiao-ran Li; Hai-yan Li; Zhong-hua Zhang; Yue Feng; Hiroko Nagano (Journal of Zhejiang University-SCIENCE B, 2012)

Effects of the Metals Lead and Zinc on the Growth, Development, and Reproduction of Pardosa Astrigera (Araneae: Lycosidae) - Xiao-qiong Chen; Zheng-tian Zhang; Ran Liu; Xiu-Ling Zhang; Jian Chen; Yu Peng (Bulletin of Environmental Contamination and Toxicology, 2011)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)